Too Many Males or Too Many Females? Classroom Sex Ratio, Life History Strategies and Risk-Taking Behaviors. - Salas-Rodríguez, Javier; Gómez-Jacinto, Luis; Hombrados-Mendieta, Isabel; Del-Pino-Brunet, Natalia (Springer, 2022)
Prior research finds that sex ratio, defined as the proportion of males and females in a given context, is related to engagement in risk-taking behaviors. However, most research operationalizes sex ratio at a local context (e.g., regional or county), which fails to reflect with precision the sex ratios contexts of individuals at a closer level. Furthermore, the relationship between sex ratio and risk-taking behaviors may be affected by individuals’ life history strategy, with previous studies showing fast life history strategies linked to risk-taking behaviors, compared to slow life history strategies. The present study analyzes the relationship between classroom sex ratio and risk-taking behaviors and the interaction between classroom sex ratio and life history strategy in adolescents. The sample comprised 1214 participants nested in 57 classrooms, 49.75% females, 91.5% Spanish and a mean age of 16.15 years (SD = 1.23, range 14–21). Results from multilevel modeling showed a negative relation between classroom sex ratio and risk-taking behaviors in female adolescents with faster life history strategy. By contrast, classroom sex ratio in male adolescents related positively to risk-taking behaviors but did not interact with life history strategy. These findings underscore the importance of studying proximate sex ratio on risk-taking behaviors in adolescents and underline its potential influence in the development and expression of life history strategies.
Keywords: Psicología evolutiva; Reducción de riesgos; Adolescentes - Psicología; Evolutionary psychology; Classroom sex ratio; Life history strategy; Risk-taking behaviors; Multilevel modeling; Adolescents